Assessing the efficiency of supply chain processes in the palm oil sector - Fitria, Nabilla; Tunjang, Hansly; Peridawaty, Peridawaty (JSM: Jurnal Sains Manajemen, 2025)
The palm oil industry remains a vital sector in Indonesia’s economy, significantly contributing to national exports and regional development. However, operating in geographically challenging areas like Kalimantan presents logistical and sustainability obstacles that demand adaptive supply chain strategies. This study aims to evaluate the supply chain efficiency of PT Triputra Agro Persada from 2019 to 2023 using the SCOR (Supply Chain Operations Reference) model, which encompasses five performance dimensions: reliability, responsiveness, agility, cost, and asset management. A quantitative descriptive-analytical method was used, supported by secondary data obtained from internal company records. The analysis shows fluctuating performance across years, with Perfect Order Fulfillment (POF) reaching 101.69% in 2019, declining sharply in 2022 to 65.30%, and recovering to 92.69% in 2023. Order Fulfillment Cycle Time (OFCT) remained relatively stable, although it slightly increased in 2023. Agility metrics improved in 2022 but weakened again in 2023 due to increased demand. The most cost-efficient year was 2022, although logistics costs rose in 2023. Meanwhile, Cash to Cash Cycle Time (C2C) improved significantly over the five-year period, indicating better asset management. The results suggest that while PT Triputra Agro Persada has achieved notable gains in supply chain performance, continued investment in technology, stakeholder collaboration, and sustainability initiatives is essential. Strategic recommendations include enhancing logistics through digital tools, strengthening inter-unit coordination, and optimizing asset utilization. This research contributes insights for palm oil companies operating in similar remote areas to balance operational efficiency with sustainability. Future studies are encouraged to integrate qualitative data and assess broader supply chain ecosystems.